Tax Accounting and Entrepreneurship Education for Students of SMK Negeri 4 Denpasar as an Effort to Improve Tax Compliance and Entrepreneurial Readiness - I Made Dwi HARMANA; I Putu Gede Satria WIRAHARJA; I Wayan Chandra ADYATMA; Ni Kadek Ditha MAHARANI; I Gusti Ayu CANDRI (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) activity is carried out in collaboration with SMK Negeri 4 Denpasar with the main objective of providing education on tax accounting and entrepreneurship. Through this activity, it is expected that the students will gain better literacy related to the understanding of basic taxation, particularly in the context of tax accounting, as well as basic entrepreneurial skills, so that they can improve their readiness to enter the workforce or create their own independent businesses. Up to this progress report period, the implementation team has completed several stages of activities, namely coordination with the school, preparation of educational materials, and the initial dissemination regarding the importance of tax accounting and entrepreneurship in the digital economy era. The response from the school and students has been very positive, as indicated by the enthusiasm of students during discussion and question-and-answer sessions. This PKM activity is designed using a combination of educational, training, and mentoring approaches. Thus, it is expected that the students will not only gain theoretical knowledge but also have practical skills that can be directly applied. In the next stage, the community service team will continue with intensive training on simple tax accounting recording and business planning simulations based on entrepreneurship. Through this activity, the expected outcomes include the improvement of taxation and entrepreneurship literacy among students of SMK Negeri 4 Denpasar, as well as the creation of a learning product in the form of a simple module that can be used sustainably by the school.